2022
DOI: 10.1101/2022.01.14.22269323
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cerebrospinal fluid neurofilament light chain differentiates behavioural variant frontotemporal dementia progressors from ‘phenocopy’ non-progressors

Abstract: Background: Distinguishing behavioural variant frontotemporal dementia (bvFTD) from non-neurodegenerative non-progressor, phenocopy mimics of frontal lobe dysfunction, can be one of the most challenging clinical dilemmas. A biomarker of neuronal injury, neurofilament light chain (NfL), could reduce misdiagnosis and delay. Methods: Cerebrospinal fluid (CSF) NfL, amyloid beta 1-42 (AB42), total and phosphorylated tau (T-tau, P-tau) levels were examined in patients with an initial diagnosis of bvFTD. Based on … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…There is also now available evidence on this biomarker in clinical settings with unselected patients [19][20][21]. In daily clinical practice, recent evidence has suggested that plasma NfL could provide guidance for etiological diagnosis of cognitive disorders despite the overlap between neurodegenerative conditions [21,22]. Large efforts are currently being made to introduce plasma NfL in clinical settings, including de ning cut-offs to identify neurodegenerative disorders and reference values for each age group [4,5].…”
mentioning
confidence: 99%
“…There is also now available evidence on this biomarker in clinical settings with unselected patients [19][20][21]. In daily clinical practice, recent evidence has suggested that plasma NfL could provide guidance for etiological diagnosis of cognitive disorders despite the overlap between neurodegenerative conditions [21,22]. Large efforts are currently being made to introduce plasma NfL in clinical settings, including de ning cut-offs to identify neurodegenerative disorders and reference values for each age group [4,5].…”
mentioning
confidence: 99%